Cal ripken, jr. eaudiobook Play ball!. - Ripken, Cal (Recorded Books Inc., 2015)
Cal Ripken, Jr. is a great baseball player. In 1995, he broke the record for playing the most consecutive games-2,632 games in a row! He has played in 16 All-Star games. And he has won many honors and awards. How did Cal Ripken, Jr. become a baseball star? In his own words, Cal tells you what it was like to grow up in a baseball family. He also talks about reaching his personal goal: to play the best he can in every game. All young readers who love baseball will find inspiration in this account of Cal Ripken, Jr.'s life and his career. Filled with great sports moments and his most memorable games, this Puffin Easy-to-Read book will also encourage listeners to explore books on their own.